Digital Literacy as a Core Competency: Preparing Students for the Future Workforce - Seeletse, Solly Matshonisa; Azizah, Suci Midsyahri; Mardhotillah, Bunga; Fathoni, Tamrin (EDUJAVARE: International Journal of Educational Research, 2024)
In the era of rapid technological advancement, digital literacy has become a fundamental competency required for success in the modern workforce. However, there remains a gap between the digital skills taught in educational settings and the competencies needed by employers. This study explores how digital literacy can be integrated as a core competency in educational systems, aiming to better prepare students for the digital-first workforce. Using a qualitative case study approach, the research involved in-depth interviews, focus group discussions, and document analysis across several educational institutions. The study found that while there is growing recognition of the importance of digital literacy, its integration remains inconsistent, with many institutions focusing primarily on technical skills rather than the broader cognitive and ethical aspects of digital literacy. Additionally, gaps in teacher training and the lack of standardized frameworks for teaching digital literacy were identified as key challenges. The study concludes that a more comprehensive and standardized approach is needed to incorporate critical thinking, ethical engagement, and adaptability to ensure students are fully prepared for the digital workforce.